A facile approach for the in vitro assembly of multimeric membrane transport proteins - Erika A Riederer; Paul J Focke; Elka R Georgieva; Nurunisa Akyuz; Kimberly Matulef; Peter P Borbat; Jack H Freed; Scott C Blanchard; Olga Boudker; Francis I Valiyaveetil (eLife, 2018)
Membrane proteins such as ion channels and transporters are frequently homomeric. The homomeric nature raises important questions regarding coupling between subunits and complicates the application of techniques such as FRET or DEER spectroscopy. These challenges can be overcome if the subunits of a homomeric protein can be independently modified for functional or spectroscopic studies. Here, we describe a general approach for in vitro assembly that can be used for the generation of heteromeric variants of homomeric membrane proteins. We establish the approach using GltPh, a glutamate transporter homolog that is trimeric in the native state. We use heteromeric GltPh transporters to directly demonstrate the lack of coupling in substrate binding and demonstrate how heteromeric transporters considerably simplify the application of DEER spectroscopy. Further, we demonstrate the general applicability of this approach by carrying out the in vitro assembly of VcINDY, a Na+-coupled succinate transporter and CLC-ec1, a Cl-/H+ antiporter.